Analysis of Effectiveness on Monte Carlo Importance Biased Transport Calculation (Communications in Computational Physics, 2010)
To obtain fine distributing calculation about the time, space and energy ofneutron flux for a kind of non-stationary particle transport problem, the scheme ofglobal Monte Carlo variance reduction is developed. In order to provide the foundationfor this scheme, it is necessary to analyze its effectiveness before putting it to use.This paper fulfills this through analyzing the effectiveness of its core which is MonteCarlo transport importance biased calculation. By decomposing the arithmetic andcalculating the representative objectives, the effectiveness of the Monte Carlo transportimportance biased calculation is demonstrated.